Metode WISE untuk Menganalisis Penerapan Keselamatan dan Kesehatan Kerja di Industri Kecil dan Menengah - Ratih Andhika Akbar Rahma (Poltekkes Kemenkes Yogyakarta, 2020)
Small and medium enterprises (SMEs) have difficulties managing occupational safety and health (OSH) in the workplaces. Besides being due to poor OSH conditions, it is also caused by a lack of systematic OSH management. Work improvement in small enterprises (WISE) is a participa- tory training program to assist small and medium businesses in increasing workplace productivity and efficiency through the application of OSH aspects. The research was aimed to analyze and evaluate the implementation of the WISE program at the gamelan craft house X in Paju, Pono- rogo. The research method used consisted of several stages, namely: literature study and field studies, and evaluation of working environment conditions using WISE checklist, and data analy- sis. The results showed that the application of OSH in the gamelan craft X was 27%. There are six critreria who need action, consisting of 17 points where 8 points require urgent action propo- sals (priority). Some priority actions proposed are to avoid placing material on the floor and pla - cing it in a particular storage area, placing separate waste containers at work for various types of waste, and placing flammable materials with secure. This research shows the low implementati- on of OSH in workplaces, especially in SMEs.